2014
DOI: 10.1016/j.scaman.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study into the influence of works council advice on managerial decision-making

Abstract: This paper experimentally studies the potential effect of works councils on managerial decision-making. Empirical evidence on the influence of works councils in organizations is still mixed. Therefore, this experimental study tries to gain more insights into the mechanisms that may underlie the impact of works council advice. First, we try to explain whether advice given by a works council influences the decision managers make. Second, we attempt to explain whether works councils delay the decision-making proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…While unemployment has well known negative psychological effects, re‐employment into low quality jobs – including those with low autonomy and high insecurity as well as low pay – may lead to even worse health outcomes (Chandola and Zhang ); again a key channel may be through chronic stress. It is perhaps surprising that the psychological and health dimensions of works councils appear to have been largely neglected (but see Jirjahn and Lange and Sapulete, van Witteloostuijn and Kaufmann for exceptions).…”
Section: Discussionmentioning
confidence: 99%
“…While unemployment has well known negative psychological effects, re‐employment into low quality jobs – including those with low autonomy and high insecurity as well as low pay – may lead to even worse health outcomes (Chandola and Zhang ); again a key channel may be through chronic stress. It is perhaps surprising that the psychological and health dimensions of works councils appear to have been largely neglected (but see Jirjahn and Lange and Sapulete, van Witteloostuijn and Kaufmann for exceptions).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, more narcissistic participants utilized advice less, particularly when controlling for extraversion (Kausel et al, 2015†). Other studies have found that more agentic decision makers are more likely to dismiss advice (Schultze et al, 2018‡), that decision makers with a lower need for cognition increase their utilization more in response to emoticons in advisory messages (Duan et al, 2018‡), and that selfish decision makers are more likely to act selfishly when receiving (selfish) advice (Coffman & Gotthard-Real, 2019†; Sapulete et al, 2014†). Participants aged 60 and older utilized advice more than those between the ages of 18 and 37, and older participants with poorer working memory and fluid intelligence were less sensitive to the quality of the advice they received (Bailey et al, 2021‡).…”
Section: Stage 2: Advice Utilizationmentioning
confidence: 99%